Management Stress On Farmers In Agricultural Areas - Enggal Hadi Kurniyawan; Dita Septia Pratiwi; Ananda Kurniasari; Kharisma Putri Sonya; Ilma Khoiro Maulidia; Kholid Rosyidi Muhammad Nur; Dicky Endrian Kurniawan (Nursing and Health Sciences Journal (NHSJ), 2024)
Farmers often experience psychosocial problems caused by stress due to crop failures and a low economy. Psychosocial issues can also occur due to constraints experienced by farmers, such as weather changes, large imports of materials, and decreased prices for food grown due to abundant crop yields. This study aims to discover the psychosocial problems in farmers caused by stress due to crop failure and a low economy. This study uses the literature review method. The search was carried out based on three databases: Science Direct, PubMed, and Google Scholar. Some of the psychosocial problems that can occur in farmers include anxiety, fatigue, loss of interest in usual activities, difficulty sleeping, and changes in body weight. Farmers can also feel lonely and isolated because they tend to do their work on the farm. In addition, farmers can also experience stress due to social pressure from the surrounding community, which requires them to be successful in farming. This can affect the mental health of farmers and exacerbate pre-existing psychosocial conditions. Farmers who work in agriculture have many economic and psychosocial risks. Among other things, farmers can be at risk of experiencing crop failure, which can cause various things. Therefore, farmers need to know how to deal with crop failure, how to prevent it, and how to cope with stress during crop failure as a first step to dealing with the risk of psychosocial disturbances in farmers due to crop failure.